2022
DOI: 10.47626/2237-6089-2020-0042
|View full text |Cite
|
Sign up to set email alerts
|

Memory bias and personality characteristics in college students with social anxiety disorder

Abstract: Introduction: Some individuals are more susceptible to recalling false information about events that never happened in their life. Nevertheless, there are several factors, such as personality characteristics, that appear to be related to memory performance. Social anxiety also provokes memory deficits for events that happen to other people, because these individuals tend to focus on their own inner selves rather than on external signs. Objective: To investigate the influence of the personality characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(73 reference statements)
0
2
0
Order By: Relevance
“… 7 If not treated in time, SAD will become chronic and progressive, seriously affecting the healthy development of personality. 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 If not treated in time, SAD will become chronic and progressive, seriously affecting the healthy development of personality. 8 …”
Section: Introductionmentioning
confidence: 99%
“…7 If not treated in time, SAD will become chronic and progressive, seriously affecting the healthy development of personality. 8 Previous studies have found that there were certain differences in epidemiological and clinical characteristics in different countries. 9 At present, with the improvement and development of psychological counseling in China, an increasing number of SAD patients are seeking help in psychological clinics.…”
Section: Introductionmentioning
confidence: 99%